Enclosure wall of the Mahanaleshwar Temple Complex - Temples of India Project Team (Jio Institute, 2024)
The enclosure wall of the Mahanaleshwar temple complex that starts from the pratoli (entrance gateway) on both sides can be seen here. The two-storeyed gateway is adorned with pyramidical canopy roof.